Partially Carbonized Polymer Binder with Polymer Dots for Silicon Anodes in Lithium‐Ion Batteries. Issue 2 (20th November 2022) - Wu, Zhuoying; Wan, Zhengwei; Li, Zeheng; Du, Qiaokun; Wu, Tong; Cao, Jun; Ling, Min; Liang, Chengdu; Tan, Yuanzhong
Abstract: Large‐scale applications of conventional conductive binders for silicon (Si) anodes are challenging to accomplish due to their complex synthesis steps and high cost. Herein, a carbonized polymer dots‐assisted polyvinyl alcohol‐chitosan (PVA‐CS‐CPDs) binder is developed through a simple and low‐cost hydrothermal method. Through rational design, the PVA‐CS‐CPDs binder retains rich polar groups while forming conjugated structures. The conjugated structure endows the PVA‐CS‐CPDs with high electronic conductivity, and the retained polar groups maintain strong binding strength. The proposed water‐soluble binding system acts as both a binder and conductive additive, enabling stable cycling for high‐Si‐content (90 wt.%) anodes without any other conductive additives. Abstract : A carbonized polymer dots‐assisted polyvinyl alcohol‐chitosan (PVA‐CS‐CPDs) binder is developed via a simple and low‐cost hydrothermal method. PVA‐CS‐CPDs is a water‐soluble colloidal system with conjugated structures that enhance electronic conductivity and rich polar functional groups that keep binding strength. The proposed binding system serves as a binder and a conductive additive, allowing stable cycling for high Si‐content anodes.